Dielectric Studies in Spherical Silica Nanoparticles doped Ferroelectric Liquid Crystal Mixture. (May 2020) - Kaur, Gagandeep; Singh, Ashwani Kumar; Yadav, Sumit; Kumar, Pankaj; Malik, Praveen
Abstract: in this paper, spherical silica nanoparticles were doped into a ferroelectric liquid crystal (FLC) material. Dielectric studies were carried out in the frequency range of 20Hz-1MHz. Temperature and frequency dependent dielectric permittivity were investigated in the undoped and doped samples. It was observed that adding a small amount of SNPs, the permittivity increases ∼20% than pure FLC mixture. A Goldstone mode was observed in both pristine FLC and SNPs doped FLC samples. The relaxation frequency of detected mode was also observed at ∼570 Hz and ∼715 Hz for pristine FLC and doped samples respectively at 34°C. A single relaxation behaviour was also described in the form of Cole-Cole plot.